Genetic diversity of the LILRB1 and LILRB2 coding regions in an admixed Brazilian population sample. (27th July 2022) - Oliveira, Maria Luiza Guimarães; Castelli, Erick C.; Veiga‐Castelli, Luciana C.; Pereira, Alison Luis E.; Marcorin, Letícia; Carratto, Thássia M. T.; Souza, Andreia S.; Andrade, Heloisa S.; Simões, Aguinaldo L.; Donadi, Eduardo A.; Courtin, David; Sabbagh, Audrey; et al.
Abstract : Leukocyte immunoglobulin (Ig)‐like receptors (LILR) LILRB1 and LILRB2 may play a pivotal role in maintaining self‐tolerance and modulating the immune response through interaction with classical and nonclassical HLA molecules. Although both diversity and natural selection patterns over HLA genes have been extensively evaluated, little information is available concerning the genetic diversity and selection signatures on the LILRB1 / 2 regions. Therefore, we identified the LILRB1 / 2 genetic diversity using next‐generation sequencing in a population sample from São Paulo State, Brazil. We identified 58 LILRB1 Single Nucleotide Variants (SNVs), which gave rise to 13 haplotypes, and 41 LILRB2 SNVs arranged into 11 haplotypes. Although we may not exclude as a possible effect of population structure, we found evidence of either positive or purifying selection on LILRB1 / 2 coding regions. Some residues in both proteins showed to be under the effect of positive selection, suggesting that amino acid replacements in these proteins resulted in beneficial functional changes. Finally, we have revealed that allelic variation (six and five amino acid exchanges in LILRB1 and LILRB2, respectively) affects the structure and/or stability of both molecules. Nonetheless, LILRB2 has shown higher average stability, with no D1/D2 residue affecting protein structure. Overall, our findings demonstrate that LILRB1 and LILRB2 are as polymorphic as HLA class Ib genes and provide strong evidence supporting the directional selection regime hypothesis.